ANALYSIS OF SAFETY MANAGEMENT PRACTICES AND QUALITY EDUCATION DELIVERY IN PUBLIC TERTIARY INSTITUTIONS IN IMO STATE, NIGERIA - Jude, opara; Idochi, Okenwe; Chibuzor, Ononogbo Martins; Chidinma, Ujah (IJRDO-Journal of Applied Science, 2018)
This study examined safety management practices as correlate of quality education delivery in public tertiary institutions in Imo State, Nigeria. Three (3) research questions and three hypotheses were formulated to guide the study. The methodology used the Ordinary Least Square (OLS) since it enabled the researcher to capture the essence of the work effectively in addition to its high level of simplicity and global acceptability. The diagnostic tests such as normality, serial correlation, heteroscedasticity and multicollinearity were all examined. The population of the study consists of all the lecturers in the four selected public tertiary institutions in Imo State, Nigeria, and a sample of size two hundred and twelve (212) was employed in this study. Research questions 1–2 were answered using Simple Pearson (r) correlation coefficient statistic, while research question 3 was answered using multiple Pearson correlation coefficient statistic. Hypotheses 1–2 were tested using simple linear regression statistic, while hypothesis 3 was tested using multiple linear regression statistic at a p< 0.05 level of significance. The findings revealed the following: there is a high significant relationship between environmental safety practices and quality education delivery in public tertiary institutions in Imo State; there is a very high significant relationship between safety training and quality education delivery in public tertiary institutions in Imo State; there is a very significant multiple linear relationships among environmental safety practices, safety training and quality education delivery in public tertiary institutions in Imo State. Based on the findings, the study recommended that: the school management should make adequate provision of safety facilities that would enhance the safety of the staff and students in public tertiary institutions in Imo State; the school management should also endeavour to ensure that the available facilities and social amenities are in good condition through adequate maintenance to ensure the safety of the staff and students in public tertiary institutions in Imo State, among others.